Domain conformations of the motor subunit of EcoR124I involved in ATPase activity and dsDNA translocation - Bialevich, Vitali (Jihočeská univerzita, 2017)
Bacterial type I restriction-modification systems are composed of three different subunits: one HsdS subunit is required for identification of target sequence and anchoring the enzyme complex on DNA; two HsdM subunits in the methyl-transferase complex serve for host genome modification accomplishing a protective function against self-degradation; two HsdR (or motor) subunits house ATP-dependent translocation and consequent cleavage of double stranded DNA activities. The crystal structure of the 120 kDa HsdR subunit of the Type I restriction-modification system EcoR124I in complex with ATP was recently reported. HsdR is organized into four approximately globular structural domains in a nearly square-planar arrangement: the N-terminal endonuclease domain, the RecA-like helicase domains 1 and 2 and the C-terminal helical domain. The near-planar arrangement of globular domains creates prominent grooves between each domain pair. The two helicase-like domains form a canonical helicase cleft in which double-stranded B-form DNA can be accommodated without steric clash. The helical domain, probably involved in complex assembly, exhibits only a few specific interactions with helicase 2 domain. Molecular mechanism of dsDNA translocation, cleavage and ATP hydrolysis has not been yet structurally investigated. Here we propose a translocation cycle of the restriction-modification system EcoR124I based on analysis of available crystal structures of superfamily 2 helicases, strutural modeling and complementary biochemical characterization of mutations introduced in sites potentially inportant for translocation in the HsdR motor subunit. Also a role of the extended region of the helicase motif III in ATPase activity of EcoR124I was probed.
Domain conformations of the motor subunit of EcoR124I involved in ATPase activity and dsDNA translocation
Keywords: DNA restriction enzymes; E. coli; Multisubunit enzyme complex; EcoR124I; HsdR; Type I R-M systems; DNA restriction enzymes; E. coli; Multisubunit enzyme complex; EcoR124I; HsdR; Type I R-M systems